MISKONSEPSI DAN KESULITAN SISWA SEKOLAH DASAR PADA PENGENALAN KONSEP ASAM BASA: KAJIAN LITERATUR - Santi Febriani; Nurul Candra Imani; Annisa Yumna Rizq; Luthfiah Hanifah; Afridha Laily Alindra (STKIP Subang, 2026)
Misconceptions about acid-base concepts are still frequently experienced by elementary school students because science learning tends to be teacher-centered and lacks concrete learning experiences. This condition causes students to have difficulty understanding the properties of acids and bases, the use of indicators, and the concept of pH scientifically. This study aims to examine the forms of misconceptions, causal factors, and learning strategies that can reduce student misconceptions about acid-base concepts. The research involves library research, which entails reviewing various sources relevant to the research topic, such as books, scientific articles, journals, and previous research findings. Data were obtained from ten scientific articles published between 2015 and 2025 that were relevant to the research topic. Data analysis was conducted using content analysis techniques through the process of grouping, comparing, and synthesizing research results. The results of the study indicate that student misconceptions often occur in understanding the properties of acids and bases, the use of indicators, and the classification of acidic, basic, and neutral substances. Students tend to understand concepts based on everyday experiences, such as assuming all acids are dangerous or all clear liquids are neutral. Factors causing misconceptions include less varied learning methods, minimal use of concrete media, and low student initial understanding. Experiment-based learning, the use of concrete media, and experiment-based Problem Based Learning and Visual, Auditory, Kinesthetic models have been proven to be effective in increasing students' conceptual understanding and reducing misconceptions in science learning in elementary schools.